O regime de aplicação das penas no campo da responsabilidade penal da pessoa jurídica nos crimes ambientais. - Rolim, Patrícia Sarmento (2017)
This paper aims to demonstrate the feasibility and effectiveness of criminal law within the scope of environmental law, in the search for a true environmental criminal law, demonstrating that it acts not only in a symbolic way, which would relieve public authorities of rethinking A policy of protection and especially of effective prevention of the environment. It was a research whose methodological procedure is of the type combined with observance of the qualitative, descriptive, explanatory and also exploratory type being directed to two strands, one of them focused on the criminal responsibility of legal entities in the ambit of environmental crimes; In the second place, directed to the complex structure imposed by the legislation regarding the application of penalties to legal entities. The dialectical method (dialectical materialism) should be observed taking into account the very contradictory aspects of the present research, where the reality will have to be analyzed from the confrontation of theories and hypotheses, as well as concepts taken as ""truth"" in order to of a new solution in its historical, cultural and social aspects. The central problem of this research emphasizes the regime of application of penalties of legal persons in crimes committed against the environment, where several other related problems are unfolded in view of the mutual dependence between them. The dosimetry of the sentence presupposes the admissibility of criminal liability of legal persons, as well as the recognition of the effectiveness of criminal law in the area of environmental law, taking into account that this is a deeply preventive nature, leaving to criminal law the difficult task of tightening the Legislation as a way to try to make ""environmental criminal law"" more effective. The main aspects related to the systematic application of penalties to collective bodies were analyzed, using, therefore, the system of penalties provided for in the Penal Code, taking into account the omissions of the Environmental Crimes Law, which despite To constitute until the present day the object of controversies and severe criticisms constitutes central theme of our research.